Social norms and household time allocation - Sevilla-Sanz, A; Fernandez, C (University of Oxford, 2006)
Economic theories of the household predict that increases in female relative human capital lead to decreases in female housework time. However, longitudinal and cross-sectional evidence seems to contradict this implication. Women's share of home time fails to decrease despite increases in women's relative earnings. The literature has proposed social norms on the household division of labor as an alternative explanation. We use the 2002-03 Spanish Time Use Survey (STUS) to explore the presence of social norms associated to the household division of housework and childcare. First, we observe that wives that earn more than their husbands still undertake more than 50% of housework and childcare. Second, we find that a woman's relative share of housework decreases as her relative earnings increase, but only up to the point when she earns the same as her husband. Finally, independently of the definition of childcare, the relative time devoted to childcare does not vary with spouses' relative earnings. All these findings suggest that social norms might be an important factor in the division of household time.